Axillary Artery Thrombosis in a Neonate In Utero: A Case Report - A. Szvetko; E. Hurrion; A. Dunn; S. Fasihullah; S. Withers (Case Reports in Pediatrics)
We describe a neonate of 38-week and 6-day gestation born by lower uterine cesarean section for breech presentation, where it was evident on delivery that there was significant edema of the right arm from the deltoid to the distal tips of the fingers. Doppler flow ultrasound revealed extensive arterial thromboembolus. Intravenous heparin was prescribed for three days at a dose of 27.5 U/kg/h, targeting an activated partial thromboplastin time (APTT) of 60–75 seconds, followed by a course of subcutaneous enoxaparin at a dose of 1.8 mg/kg and then 2 mg/kg twice daily, titrated to a factor Xa level of 0.5–1.0 U/mL for another three days. Significant clinical improvement occurred and the child was eventually, discharged on subcutaneous enoxaparin. Magnetic resonance imaging showed multiple intracranial abnormalities. At five months increased upper limb tone, brisk reflexes, and small head circumference were noted. At one year, increased tone and increased paucity of movement on the right side persisted, and some speech delay and visual inattention were noted. Recent follow-up at 16.5 months of age demonstrated a right sided hemiplegia with increased tone and brisk reflexes. We describe the case in detail and review current knowledge regarding the management of arterial thrombosis in the neonate.